Reading Development, Word Length and Frequency Effects: An Eye-Tracking Study with Slow and Fast Readers - Gerth, Sabrina; Festman, Julia (Frontiers in Communication, 2021)
Research on reading development attempts to explain differences in the reading patterns of adults and children. Previous studies, which typically analyzed word length and frequency effects in developing readers, often focused on dyslexic or dysfluent readers. Similar to previous studies, we investigated the effects of word length and word frequency on the eye movements of children and added several novel aspects: We tested 66 typically developing German-speaking children. Children’s oral reading fluency was used as measure of reading ability. Only fast readers (n = 34, mean age 10.9 ± 0.9 years) and slow readers (n = 32, 11.2 ± 0.9 years) participated in an eye-tracking experiment and silently read an age-appropriate original narrative text from a children’s book. The analysis of silent reading of the entire text confirmed the earlier group classification. To analyze word length and frequency, we selected 40 nouns as target words in the text. We found significant effects of word length and word frequency for all children in the expected direction. For fast readers, we detected significant interactions of word length and frequency in first fixation duration, gaze duration, and total reading time. These revealed a frequency effect for long, but not short words. This suggests lexical whole-word processing with a fast activation of the word’s lexical entry for shorter words and an application of the nonlexical route of the dual route cascaded model (DRC) with a slower lexical access to whole word forms for long words. Slow readers demonstrated a strong sensitivity to word length, indicating a slower or delayed lexical access to orthographic word forms. Additionally, they exhibited weaker word frequency effects. These findings suggest a developmental view of reading in typically developing children in accordance with the DRC, with nonlexical serial decoding as the seemingly prominent reading strategy of slow readers and lexical whole-word recognition as the prominent reading strategy of fast readers.